Qur'anic Values as a Foundation for Social Change in Modern Society - Djidin, M (IQRO: Journal of Islamic Education, 2024)
The Qur'ān as the holy book of Muslims has a significant role in shaping the social fabric of society. This study aims to explore the relationship between the Qur'ān and social change, focusing on how Qur'ānic teachings influence social transformation in various aspects of life. This research uses a qualitative method with a thematic interpretation approach that collects relevant verses to explore the relationship between the Qur'an and social change. The primary data sources are Qur'anic verses that explicitly or implicitly discuss concepts related to social change. The Qur'anic verses were selected based on their relevance to themes such as justice, collective responsibility, social care. The results show that the Qur'an provides a strong ethical foundation for sustainable and equitable social change. Concepts such as amar ma'ruf nahi munkar, social justice and collective responsibility are seen as key drivers in driving positive change in society. In addition, the Qur'an emphasizes the importance of education, tolerance and dialogue between communities as key pillars in dealing with social challenges. These teachings are relevant to apply in the modern context, where society continues to evolve with the challenges of globalization, moral crisis and inequality. This study concludes that the Qur'an is not only a spiritual guide, but also a practical guide in creating constructive social change. Thus, a deep understanding of the teachings of the Qur'an is needed so that Muslims can actively contribute to an equitable and inclusive social transformation process. This research is expected to enrich the academic discourse on the role of religion in social change and offer new insights into the relevance of the Qur'an in the contemporary socio-cultural context.